Decolonization in the Field? Basel – Milingimbi Back and Forth - Voirol, Beatrice (Swiss Journal of Sociocultural Anthropology, 2019)
With regard to decolonization, ethnographic museums are special targets for criticism. For a long time they pursued "salvage ethnography", taking advantage of colonial structures to assemble their collections. The little island of Milingimbi in East Arnhem Land/ Australia first attracted the attention of the Museum der Kulturen Basel (MKB) in the early 1930s. Three different individuals were involved in compiling the collection as it is constituted today, one of the largest collections from Milingimbi outside of Australia. Taking this collection as an example, my contribution takes a closer look at decolonizing practices in the museum field. It retraces the transition from collecting under colonial conditions to current attempts within the MKB to decolonize the Milingimbi collection. The article describes the practical e orts not only of MKB as an institution, but particularly also of Milingimbi as a community.